2-aminopyrimidin-1-ium trichloroacetate - Hu, M.L.; Ng, Seik Weng; Zain, Sharifuddin Md; Ye, M.D. (International Union of Crystallography, 2002)
The 2-aminopyrimidin-1-ium trichloroacetate ion-pairs in the title compound, C4H6N3+.C2Cl3O2-, are held together by two N-H...O hydrogen bonds [N-amino...O = 2.733 (5); N-pyrimidinium...O = 2.783 (6) Angstrom], and adjacent ion-pairs are linked into a linear helical chain by a third and substantially weaker N-H...O hydrogen bond [N...O = 3.026 (3) Angstrom]. The calculated structure of the ion-pair geometry, optimized at the PM3 level, shows good agreement with the experimental results.